EFEKTIVITAS PENGEMBANGAN KEPROFESIAN BERKELANJUTAN UNTUK GURU - Nurkolis Siri Kastawi; Yovitha Yuliejantiningsih; Sunandar Sunandar (Universitas Kristen Satya Wacana, 2017)
The main problem in this article is how effective of continuity professional development (CPD) implementation for teachers. This study used a descriptive qualitative approach in Demak District Central Java Province. Demak Regency is a district that implemented the CPD seriously so that containing Regents Regulation, RPJMD, and Strategic Planning of Education Office. Data collection using interviews and documentation. Research result showed that CPD implementation have been running effectively. Three indicators found: regulations governing CPD implementation, details of the CPD programs and activities, and controlling of CPD regulation with programs and activities. The CPD implementation in Demak District can be implemented in forms: structured training activities, workshops, seminars, others scientific meeting; mentoring for teacher and headmaster conducted by facilitators; activities at professional learning community; and induction program or internship of beginner to advance. In order to make implementation of CPD more effectively so needs regulatory refinements.